Planning of the Arab-Islamic city of privacy and modernity - الكناني, أ.د.كامل كاظم بشير (Journal of Planner and Development, 2006)
Each Arab Islamic city is distinguished by its distinctive characteristics dictated by the nature of its location and its characteristics, as we see it mountainous in the mountains, deserts in the deserts, and coastal in the coasts, and this is reflected in the models of its buildings and designs and even in its structure. However, this uniqueness did not stand in the way of the emergence of characteristics and common characteristics of these cities over time, the factors derived from the core of the life of the community habits and traditions and beliefs and living requirements and environmental conditions that all piled in the process of building and construction of the Arab Islamic city to draw The features and lines of life of the community on the architecture and vocabulary and then give them their own language and distinctive. The Arab city is a living being that is influenced and influenced, takes and gives a living to the year of life, which has different ages and circumstances. This trend helps us a lot in revealing the authenticity of this city or the value of its value, which formed its physical container in the perfect harmony crystallized in the end the image of the city, the mosque, the arena, the field, the market and the inner courtyard are the original features of the Arab Islamic city, The large expansions witnessed in most Islamic cities have affected these features and overlapped the uses of the land in different styles from the traditional style, especially the urban urban style. This effect has lost the city's uniqueness due to factors such as technical, economic and other social and environmental factors in determining these patterns Over time periods of expansion and growth of the Arab Islamic city, which requires efforts to re-understand more of the nature of what should be the planning of this city in their ability to interact neighborhood associated with air conditioning with the requirements of the age in the framework of privacy required